Pd Nanoparticle Assemblies as Efficient Catalysts for the Hydrogen Evolution and Oxygen Reduction Reactions. Issue 3 (3rd January 2017) - Liu, Suli; Mu, Xueqin; Duan, Huiyu; Chen, Changyun; Zhang, Hui
Abstract : Developing bifunctional catalysts for both the hydrogen evolution reaction (HER) and the oxygen reduction reaction (ORR) is crucial for obtaining hydrogen easily by water splitting to promote electrochemical energy conversion in fuel cells. In this paper, we report a facile approach for the synthesis of Pd nanoparticle assemblies (NPAs) with porous structure as catalysts for both the HER and the ORR with desirable electrocatalytic activities and long‐term stability. For the HER, the porous Pd NPAs exhibit a low onset potential, a small Tafel slope of 30 mV dec –1, and an exceptionally low overpotential of about 80 mV at a current density of 100 mA cm –2, and these porous Pd NPAs maintain their catalytic activity for at least 1000 cyclic voltammetry (CV) cycles of durability in 0.5m H2 SO4 . As for the ORR, the porous Pd NPAs offer a remarkable catalytic activity with a diffusion‐limiting current density of 3.85 mA cm –2, a half‐potential of 0.837 V, and an onset potential of 0.926 V at 1600 rpm with a scan rate of 5 mV s –1 . This study enables the design of novel bifunctional electrocatalysts in the renewable energy field. Abstract : The porous Pd nanoparticle assemblies (NPAs) prepared by the facile approach reported exhibit excellent electrocatalytic performance for the hydrogen evolution reaction (HER) and the oxygen reduction reaction (ORR), close to that of commercial Pt/C catalysts and the most reported non‐Pt‐based catalysts.